Development of palm pool brondonal pick up tools to increase time efficiency by VDI 2221 method - Lucitasari, Dyah Rachmawati; Ramadhani, Fidah Jihad (OPSI, 2024)
Koperasi Unit Desa (KUD) aims to improve the welfare of members by carrying out harvesting process activities in Lubuk Kembang Sari, Riau. The problem that often occurs is collecting oil palm fruit which is still done manually by bending or squatting. Previously there was a manual tool which had shortcomings in the form of the design of the chute section which was still less than optimal in the trajectory of throwing the brochures into the container, sometimes the brochures were thrown upwards instead of backwards into the reservoir. Another drawback is that when carrying tools if the distance is quite far then this process is a little difficult. The aim of this research is to develop a loose picker tool from existing design references to increase time efficiency.The development of tools for picking up palm oil loose ends was carried out using the VDI (Verein Deuscher Ingenieure) 2221 method. Development using this method began with analyzing the shortcomings of existing tools and developing farmers' desires and needs for the specifications of new oil palm loose picking tools. After the design concept is created, the next step is to create a customized design using the user's body anthropometry, and the final step is to carry out trials on the palm oil harvester picking tool.This research resulted in a new palm oil harvester tool that is capable of picking up palm oil stalks. The comparison between manual collection and the new tool is that the new tool can speed up the collection time by 28%. A time comparison was also made using the old tool with the new tool, it turns out that the new tool can speed up the time by 54%. Based on user satisfaction tests, the tool is easy for users to operate and is automatic.Keywords: Palm oil fruit, manual tools, time efficiency, VDI 2221